2014
DOI: 10.1155/2014/580359
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Resistance of Coagulase-Negative Staphylococci in Total Hip Arthroplasty Infections: 278 THA-Revisions due to Infection Reported to the Norwegian Arthroplasty Register from 1993 to 2007

Abstract: We investigated bacterial findings from intraoperative tissue samples taken during revision due to infection after total hip arthroplasty (THA). The aim was to investigate whether the susceptibility patterns changed during the period from 1993 through 2007. Reported revisions due to infection in the Norwegian Arthroplasty Register (NAR) were identified, and 10 representative hospitals in Norway were visited. All relevant information on patients reported to the NAR for a revision due to infection, including bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 25 publications
3
22
0
1
Order By: Relevance
“…This correlates with previous reports from Denmark, which found that the incidence of MRSA in Denmark remains low despite an increase in recent years 42 (approximately 1.7% of tested S. aureus being MRSA in Denmark compared with 18% in Europe as a whole 43 ). Other studies of bacteria identified from arthroplasty revisions in Scandinavia have found a similarly low prevalence of MRSA 6,7,39 . The discrepancy between the relative risk of PJI incidence estimated by DHR data separately and the relative risk estimated by microbiology separately was surprising.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…This correlates with previous reports from Denmark, which found that the incidence of MRSA in Denmark remains low despite an increase in recent years 42 (approximately 1.7% of tested S. aureus being MRSA in Denmark compared with 18% in Europe as a whole 43 ). Other studies of bacteria identified from arthroplasty revisions in Scandinavia have found a similarly low prevalence of MRSA 6,7,39 . The discrepancy between the relative risk of PJI incidence estimated by DHR data separately and the relative risk estimated by microbiology separately was surprising.…”
Section: Discussionmentioning
confidence: 71%
“…A suggested explanation for the increasing incidence of PJI reported from the 1990's to the beginning of the twenty first century is an increase in antimicrobial resistance 5 . Several studies, without linkage with arthroplasty registers, have identified an increase in beta-lactam-resistant CoNS during this period 6,7 . We did not detect a change in antimicrobial resistance in our study e despite a similar study design and size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among hospital CoNS isolates, the resistance pattern is markedly different (8,10,25). A Norwegian study on antimicrobial resistance patterns of clinical CoNS isolates from total hip arthroplasty infections during 1993-2007 reported an increase in methicillin resistance rates from 57 to 84%, as well as increasing rates of resistance to most other antimicrobials tested (26). Antimicrobial resistance is, however, not routinely monitored in commensal CoNS and we do not know if the prevalence of resistance in the community has increased.…”
Section: Discussionmentioning
confidence: 98%